An Assessment of the Interaction between Carbon Dioxide Emissions and Available Nutrients from the Lifecycle of Several Agricultural Crops - Prodipto Bishnu Angon; Md. Mahbubur Rahman Khan; Sadia Haque Tonny (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Agricultural products cause the emission of certain significant amount of greenhouse gases. Carbon dioxide (CO2) is one of the most important greenhouse gases and its emissions are increasing day by day as a result of the increase in agricultural productivity. This study aims to pinpoint the most environmentally friendly crops and fruits that are sources of good nutrients and emits less CO2 throughout their life cycles. Relation between nutrient availability and CO2 emissions from staple foods namely; wheat, maize, rice, potato, sugarcane, sugar beet, soybean, palm oil, sunflower, rapeseed, banana, apple and grape are investigated in this study. Secondary data was collected from dataset’s website. Spearman's rank and diagram interpretation technique are used to find out the correlation between nutrient availability and CO2 emissions. Among carbohydrate diets, rice emits 4 kg CO2 kg-1 of crops, which is significantly higher than that of wheat, maize and potato. However, the amount of carbohydrates in rice (0.26%) is less than those carbohydrate diets. Similarly, sugarcane emits more CO2 as 2.6 kg kg-1 of crops than sugar beet (1.4 kg kg-1 of crops) among sugar crops. Soybean and palm oil emit more CO2 as 6 kg kg-1 and 7.2 kg kg-1 of crops, respectively, as compared to other oilseed crops, but every oilseed crop has the same food value. Among fruits, bananas emit less CO2 (1.1 kg kg-1 of crops) and have a higher content of carbohydrates (0.23%) than other selected fruits. Proper crop selection based on nutrient content can lead to lower CO2 emissions than at present and a consistent balance between environmental and nutritional needs in the future.